Floristic Inventory of Ankasamudra Bird Conservation Reserve: A Wetland of Kalyana Karnataka, India - Siddeshwari, M.; Ramesh, Chaitra S.; Rohid Dharani, K. (Indian Forester, 2024)
The first Bird conservation reserve in the Kalyana Karnataka is the Ankasamudra Bird conservation reserve. The current paper describes the vegetation composition and its contribution to the Sanctuary as a bird habitat. An extensive floristic survey has been carried out from April 2023 to October 2023. Total 124 plants species belongs to 43 families and 54 genera. Fabaceace stands first with 24(17.64%) followed by Poaceae - with 9(6.61%) and Euphorbiaceae with 8(5.88%) species. Among habit herbs are dominant with 75(62%) followed by shrub with 20(17%) and Trees with 19(15%) and climbers with 11 species (8%). Cultivated species were 10(6.45%) and wild were 114 species (93.54%). About 42 species falls under IUCN category, least concerned were 41 (33.8%) and vulnerable is represented by single species. Among trees, the tank is dominated by Vachellia nilotica (L.) P.J.H. Hurter & Mabb., which serves breeding & roosting ground for the water birds. The aquatic system is facing threat from proliferation of Typha angustifolia Bory & Chaub. And Eichhornia crassipes (Mart.) Solms., Strategic eradication of invasive plant species and the plantation of native species in the sanctuary are needed for better management.